Comic drunks, crazy cults, and lovable monsters : bad behavior on American television - Diffrient, David Scott, 1972- (Syracuse University Press, 2022)
"Diffrient explores the ways in which social imaginaries related to "bad behavior" have been humorously exploited over the years through his examination of a broad range of network and cable TV shows across the history of the medium"-- Provided by publisher.
Keywords: Television comedies -- United States -- History and criticism.; Deviant behavior on television.; Conduct of life on television.; Comédies télévisées -- États-Unis -- Histoire et critique.; PERFORMING ARTS / Television / History & Criticism; Deviant behavior on television; Conduct of life on television; Television comedies; United States; United States.; Criticism, interpretation, etc.; Television criticism and reviews; Television criticism and reviews.; Critiques d'émissions télévisées.